Compound dry and hot extremes and their implications for fire activity over the Orinoco River Basin in northern South America (2025)
Compound dry and hot extremes (CDHE) have gained a pronounced relevance due to the observed increase in their frequency and the severity of their impacts on natural and human systems. The Orinoco River Basin, an ecoregion of great importance given its high biodiversity and the third largest river basin in South America, is vulnerable to these compound extremes because its extensive savannas are highly prone to fire activity. Here, we analyzed the occurrence of CDHE in this basin during the period 1981–2021. We compared different surface and atmospheric variables during drought periods (dry extremes) and CDHE (defined as periods with abnormally hot conditions during a meteorological drought event). Our results show that CDHE exhibit a larger precipitation deficit than dry extremes, exacerbating the meteorological drought. This stronger precipitation deficit is a response of weaker trade winds transporting moisture toward the region, in addition to stronger mid-tropospheric anticyclonic structures over the north Atlantic Ocean and the Caribbean Sea that advect dry air masses, inducing a deficit in total column water vapor and relative humidity at the mid-levels over the Orinoco. The moisture deficit during CDHE is also felt over the landmass, not only at surface but also deep soil layers, exacerbating the agricultural and ecological drought. Moreover, the decreased cloud cover associated with the enhanced precipitation deficit during CDHE increases the solar radiation reaching the surface, raising land temperature and reinforcing the drought impacts. Therefore, fire activity over the basin is enhanced during CDHE, increasing their associated burned area. This is very relevant since the savannas of the Orinoco are highly flammable and prone to fire, being burned with high frequency due to the practice of extensive livestock farming.